Major differential gene regulation in Coxiella burnetii between in vivo and in vitro cultivation models. (December 2015) - Kuley, Runa; Bossers-deVries, Ruth; Smith, Hilde; Smits, Mari; Roest, Hendrik; Bossers, Alex
Abstract Background Coxiella burnetii is the causative agent of the zoonotic disease Q fever. As it is an intracellular pathogen, infection byC. burnetii requires adaptation to its eukaryotic host and intracellular environment. The recently developed cell-free medium also allows the bacteria to propagate without host cells, maintaining its infection potential. The adaptation to different hosts or extracellular environments has been assumed to involve genome-wide modulation ofC. burnetii gene expression. However, little is currently known about these adaptation events which are critical for understanding the intracellular survival ofC. burnetii . Results We studiedC. burnetii genome–wide transcriptional patterns in vivo (mice spleen) and in cell and cell-free in vitro culture models to examine its metabolic pathways and virulence associated gene expression patterns that are required to colonize and persist in different environments. Within each model, the gene expression profiles of the DutchC. burnetii outbreak strain (602) and NM reference strains were largely similar. In contrast, modulation of gene-expression was strongly influenced by the cultivation method, indicating adaptation of the bacterium to available components. Genome–wide expression profiles ofC. burnetii from in vitro cell culture were more similar to those seen for in vivo conditions, while gene expression profiles of cell-free culture were more distant to in vivo. Under in vivo conditions, significant alterations of genes involved in metabolism and virulence were identified. We observed thatC. burnetii under in vivo conditions predominantly uses glucose as a carbon source (mostly for biosynthetic processes) and fatty acids for energy generation.C. burnetii experienced nutrient limitation and anaerobiosis as major stressors, while phosphate limitation was identified as an important signal for intracellular growth inside eukaryotic host cells. Finally, the in vivo environment significantly induced expression of several virulence genes, including those implicated in LPS synthesis, colonization, host component modulation and DNA repair mechanisms. Conclusion Our study shows thatC. burnetii, with its relative small genome, requires only a subset of core gene functions to survive under in vitro conditions, but requires the induction of full repertoire of genes for successful pathogenesis and thriving in harsh environments in vivo.